2004
DOI: 10.1128/mcb.24.22.9705-9725.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Retinoid X Receptor Regulates Nur77/Thyroid Hormone Receptor 3-Dependent Apoptosis by Modulating Its Nuclear Export and Mitochondrial Targeting

Abstract: Retinoid X receptor (RXR) plays a central role in the regulation of intracellular receptor signaling pathways by acting as a ubiquitous heterodimerization partner of many nuclear receptors, including the orphan receptor Nur77 (also known as thyroid hormone receptor 3 or NGFI-B), which translocates from the nucleus to mitochondria, where it interacts with Bcl-2 to induce apoptosis. Here, we report that RXR␣ is required for nuclear export and mitochondrial targeting of Nur77 through their unique heterodimerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
111
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 97 publications
5
111
0
Order By: Relevance
“…We previously reported that AHPN and its analog (E)-4-[3-(1-adamantyl)-4-hydroxyphenyl]-3-chlorocinnamic acid (3-Cl-AHPC) induced Nur77 mitochondrial targeting in prostate cancer and lung cancer cells (Dawson et al, 2001;Kolluri et al, 2003;Cao et al, 2004). Similar results were shown in ovarian cancer cells (Holmes et al, 2002(Holmes et al, , 2003.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…We previously reported that AHPN and its analog (E)-4-[3-(1-adamantyl)-4-hydroxyphenyl]-3-chlorocinnamic acid (3-Cl-AHPC) induced Nur77 mitochondrial targeting in prostate cancer and lung cancer cells (Dawson et al, 2001;Kolluri et al, 2003;Cao et al, 2004). Similar results were shown in ovarian cancer cells (Holmes et al, 2002(Holmes et al, , 2003.…”
Section: Introductionmentioning
confidence: 57%
“…To study whether JNK phosphorylation of Nur77 plays a role in mediating the effect of 3-Cl-AHPC on inducing Nur77 nuclear export and Nur77-dependent apoptosis (Dawson et al, 2001;Kolluri et al, 2003;Cao et al, 2004), we examined the effect of 3-Cl-AHPC on JNK activation. A panel of cancer cell lines, including H460, H292 and A549 lung cancer, LNCaP prostate cancer, and MDA-MB-231 breast cancer cells, were treated with 3-Cl-AHPC, and the activation of JNK was evaluated by an in vitro JNK kinase assay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations